Standardisation vs. adaption: a conjoint experiment on the influence of psychic, cultural and geographical distance on international marketing mix decisions. (2016) - Kraus, Sascha; Meier, Fabian; Eggers, Felix; Bouncken, Ricarda B.; Schuessler, Felix
This paper delivers new insights into how psychic, cultural and geographical distance influence international marketing mix decisions on the basis of a choice-based conjoint analysis with 96 managers from Switzerland and Liechtenstein. In this experiment, the managers had to decide whether the four Ps of the marketing mix have to be adapted or standardised for international markets (neighbouring country/European country/non-European country). Overall we found that psychic, cultural and geographical distance have a significant moderating effect on the degree of marketing mix adaptation: the larger the distance towards a market, the more inclined the managers are to make a decision that involves a larger degree of adaptation of the four Ps towards the simulated markets. The marketing mix elements product and promotion tend mostly to be adapted when cultural distance increases, while the elements price and distribution are more adapted when psychic distance is high.